Transfer RNAs are Linked to Ischemic Stroke and Major Bleeding in Patients with End-Stage Kidney Disease - Nopp, Stephan; Königsbrügge, Oliver; Schmaldienst, Sabine; Säemann, Marcus; Pabinger, Ingrid; Nossent, Anne Yaël; Ay, Cihan (Thrombosis and Haemostasis, 2024)
Background Patients with end-stage kidney disease (ESKD) are at very high risk for thromboembolism and bleeding. This study aimed to identify small noncoding RNAs (sncRNAs), specifically microRNAs and transfer-RNA (tRNA)-derived fragments (tRFs), as potential novel biomarkers for predicting thromboembolism and bleeding in this high-risk population.Methods In this sncRNA discovery research, we leveraged the VIVALDI cohort, consisting of 625 ESKD patients on hemodialysis, to conduct two nested case–control studies, each comprising 18 participants. The primary outcomes were ischemic stroke in the first study and major bleeding in the second. Plasma samples were processed using the miND pipeline for RNA-seq analysis to investigate differential expression of microRNAs and tRNA/tRFs between cases and their respective matched controls, with results stringently adjusted for the false discovery rate (FDR).Results No significant differential expression of microRNAs for either ischemic stroke or major bleeding outcomes was observed in the two nested case–control studies. However, we identified four tRNAs significantly differentially expressed in ischemic stroke cases and seven in major bleeding cases, compared with controls (FDR < 0.1). Coverage plots indicated that specific tRNA fragments (tRFs), rather than full-length tRNAs, were detected, however. Alternative mapping approaches revealed challenges and technical limitations that precluded in-depth differential expression analyses on these specific tRFs. Yet, they also underscored the potential of tRNAs and tRFs as markers for thromboembolism and bleeding.Conclusion While microRNAs did not show significant differential expression, our study identifies specific tRNAs/tRFs as potential novel biomarkers for ischemic stroke and major bleeding in ESKD patients.
Keywords: microRNAs; kidney diseases; thromboembolism; hemostasis; biomarkers; tRNAs; RNA-seq analysis